Cognitive Pattern Recognition for Enhancing the Brand of Higher Education Institutions with a Mixed Approach - Abolhasani Targhi, Fatemeh; Hataminasab, Seyed Hasan; Soltanifar, Mohammad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: In recent years, the existing problems in higher education institutions on one hand, and the increase in competition among these institutions for attracting students on the other hand, have seriously challenged their capacity fulfillment. Considering the popularity and development of social networks and their marketing capabilities, this research aims to identify a model that can enhance the brand of higher education centers.Methodology: This study was conducted in four stages (the first two stages qualitatively and the next two quantitatively) using a mixed approach. Initially, through scientometrics, relevant and authoritative documents and articles related to brand enhancement in educational centers were identified, and the most important actions were recognized through qualitative content analysis and inferential methods. Then, using a quantitative approach, the related model was identified through fuzzy screening validation and fuzzy cognitive mapping method. The methodology of this research is applied in nature, mixed in the qualitative part, and descriptive-survey in the quantitative part. The qualitative section's population was documents and records, and in the quantitative section, experts were targeted, with samples collected purposively in both sections.Findings: As a result, the qualitative part identified nine essential factors, with "recognition" determined as the initial action and "strategy and management style" as the final action based on the derived model.Conclusion: Therefore, it is necessary for stakeholders (researchers, research centers, and related organizations) to pay more attention to these two areas. One of the main reasons for advancements in international educational centers has been the focus on social media marketing and, of course, branding and brand management.